Pemanfaatan Limbah Buah Salak Pondoh Sebagai Substrat Nata De Salacca Melalui Aplikasi Bioteknologi di Dusun Tegal Domban, Sleman, Yogyakarta - Rarastoeti Pratiwi; Fajar Budi Lestari; Donny Widianto (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2015)
Dusun Tegal Domban is one of the highest Salak Pondoh produce in Sleman District. However there is a problemfaced by salak farmers due to the overproduction and overripe which mightcause waste. Implementation of Biotechnology should be one of the alternativesolutions to overcome this problem. The aims of the program were to utilize the salak fruits wasteto produce Natade Salaccausing biological agents, such as Acetobacter xylinum, and to implement the education for sustainability development which subjected toa women organization PKK Dusun Tegal Domban who accompanyed by the team from Biotechnology Master Program UGM in order to learn how to produce Nata de Salacca. This program was initiated with the laboratory experiments to find the fine composotion of nata substrates to get the optimal nata product. The following action was to acompany the women who aplicate the nata production process. Results from the laboratory experiment showed that the best composition of substrat and water ratiowas 1:4, and the nata thickness was 0.62 cm, while the nata weight was 542.22 g. Those parameters were used for nata standard indicators.Results from the activities of nata production by women groups PKK Dusun Tegal Domban were showed the similar results with the nata standard for thickness, however nata weight was slightly lower than the nata standard.